2006
DOI: 10.1021/mp060034z
|View full text |Cite
|
Sign up to set email alerts
|

Discovering H-Bonding Rules in Crystals with Inductive Logic Programming

Abstract: In the domain of crystal engineering, various schemes have been proposed for the classification of hydrogen bonding (H-bonding) patterns observed in 3D crystal structures. In this study, the aim is to complement these schemes with rules that predict H-bonding in crystals from 2D structural information only. Modern computational power and the advances in inductive logic programming (ILP) can now provide computational chemistry with the opportunity for extracting structure-specific rules from large databases tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Note that diminishing marginal returns are to be expected as performance increases. The ROC 50 results confirm that the augmen- 6 Note that we have here abused the notation and consider e = 1−AUROC rather than e = 1−accuracy Note that the WDK results reported in Table 2 are worse than those obtained by Ceroni et al…”
Section: Resultssupporting
confidence: 63%
“…Note that diminishing marginal returns are to be expected as performance increases. The ROC 50 results confirm that the augmen- 6 Note that we have here abused the notation and consider e = 1−AUROC rather than e = 1−accuracy Note that the WDK results reported in Table 2 are worse than those obtained by Ceroni et al…”
Section: Resultssupporting
confidence: 63%
“…−7.1 kcal/mol, was regarded as a reference value. The binding energy information together with other required chemical information was fed in the DMax Chemistry Assistant (DCA) software 18 to generate the inhibitor binding model. The generated inhibitor model suggested that compounds containing methyl, amide (thioamides, etc.…”
Section: Resultsmentioning
confidence: 99%
“…In this ligand-based VS study, inductive logic programming (ILP) was used to develop molecular search patterns, and molecular docking was performed to estimate the binding affinities of potential SIRT1 ligands. ILP can consider specific characteristics of compounds and human-generated rules as background knowledge to outperform traditional approaches 18 .…”
mentioning
confidence: 99%
“…Listing 4 shows a kLog script for the Bursi domain. Relevant predicates in the extensional database are a/2, b/3 (atoms and bonds, respectively, extracted from the chemical structure), sub/3 (functional groups, computed by DMax Chemistry Assistant [55,56]), fused/3, connected/4 (direct connection between two functional groups), linked/4 (connection between functional groups via an aliphatic chain). Aromaticity (used in the bond-type property of b/3) was also computed by DMax Chemistry Assistant.…”
Section: Predicting a Single Property Of One Interpretationmentioning
confidence: 99%